Anti bacterial effect of activated carbons prepared from some biomasses available in North East India. Issue 2 (15th June 2022) - Das, Joydeep; Debnath, Chandrani; Nath, Harjeet; Saxena, Rishabh
ABSTRACT: In the current study, activated carbons (ACs) prepared from some biomasses available in North East India were tested for its antibacterial capacity. The biomasses used for the preparation of ACs were rubber wood (Hevea brasiliensis), ramie fiber (Boehmeria nivea) and areca catechu husk (Areca catechu) which are basically lignocellulosic in nature and were selected depending on its robust availability in this part of the country. The ACs showed good bactericidal or killing percentage against the commonly available waterborne pathogen Escherichia coli (around 43%) even without incorporation of any metals in it. The ACs were prepared using a modified chemical and physical activation process which were found to be both highly porous (346.02 to 1998.03 m 2 /gm) and also possess sharp pointed structure in it which could puncture the bacterial cell wall. Various analytical methods like FTIR, SEM, FESEM, UV-Visible Spectroscopy, BET, and DSC were used to characterize the AC samples. This study will provide further insight into the preparation and utilization of specially prepared ACs which can directly be used for water purification purposes.